The XXL Survey XIV. AAOmega Redshifts for the Southern XXL Field. (2016) - Lidman, C.; Ardila, F.; Owers, M.; Adami, C.; Chiappetti, L.; Civano, F.; Elyiv, A.; Finet, F.; Fotopoulou, S.; Goulding, A.; Koulouridis, E.; Melnyk, O.; et al.
Abstract: We present a catalogue containing the redshifts of 3 660 X-ray selected targets in the XXL southern field. The redshifts were obtained with the AAOmega spectrograph and 2dF fibre positioner on the Anglo-Australian Telescope. The catalogue contains 1 515 broad line AGN, 528 stars, and redshifts for 41 out of the 49 brightest X-ray selected clusters in the XXL southern field.